2015
DOI: 10.1094/cchem-03-15-0058-r
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Differences in Anthocyanins from Blue‐ and Purple‐Grained Spring Wheat Grown in Four Environments in Central Saskatchewan

Abstract: Cereal Chem. 93(1):32-38Anthocyanins are important dietary components that play significant roles in human health because of their antioxidant and anti-inflammatory properties. In the present study nine anthocyanin-pigmented spring wheat lines grown at two sites in central Saskatchewan, Canada, were evaluated in terms of anthocyanin composition in comparison with four wheat checks over a two-year period. The genotypes studied were blue-aleurone and purple-pericarp wheat. The anthocyanin pigments were quantifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 33 publications
5
17
1
Order By: Relevance
“…The chromosome substitution led to increasing TAC in the bran fraction of the developed line, up to 475.7 µg/g, which was higher than in the purple-grained line (355.6 µg/g). These results are in good agreement with previously obtained data of the TAC from colored wheat grains [5,6,26,50,51]. Although TAC was higher in the blue-grained s:S294Th(4D) line compared to the purple-grained NIL and red-grained parental cv.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The chromosome substitution led to increasing TAC in the bran fraction of the developed line, up to 475.7 µg/g, which was higher than in the purple-grained line (355.6 µg/g). These results are in good agreement with previously obtained data of the TAC from colored wheat grains [5,6,26,50,51]. Although TAC was higher in the blue-grained s:S294Th(4D) line compared to the purple-grained NIL and red-grained parental cv.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the sugar moiety attached to the anthocyanins aglycones influences the free-radical scavenging capacity of anthocyanins, with higher ability shown in rutinoside-containing anthocyanins compared to glucoside-containing pigments. Other components of the bran fraction, such as phenolic acids or polymeric proanthocyanidins from testa, can also contribute to TAA [25,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In wheat bran of a purple and blue grained wheat grown from 1996 to 1998 in Canada on average 235.9 and 452.9 µg g −1 , respectively, were reported [ 20 ]. Similar values were stated by the same group in later studies: 321 and/or 405 µg g −1 for blue wheat bran [ 21 ] and 154 to 285 µg g −1 for purple wheat bran [ 22 ]. Siebenhandl et al [ 1 ] observed 168.6 and 225.8 µg g −1 for the bran and shorts fraction of Austrian purple and blue wheat, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…This facilitates breeding progress. In a more recent study with nine purple wheat genotypes in Saskatchewan, Canada, the content and composition of anthocyanin was significantly influenced by genotype and genotype by environment (G × E) interaction [19]. The source-sink relationship has an important role in anthocyanin content [20].…”
Section: Introductionmentioning
confidence: 99%